Hydroxamic acid series and their metal complexes: synthesis, characterization, cytotoxicity and neurotoxicity study / Siti Noriah Mohd Shotor - Mohd Shotor, Siti Noriah (2014)
The synthesis and characterization of a series of hydroxamic acid namely benzohydroxamic acid (BHA), salicylhydroxamic acid (SHA) and their complexes with Cu(II), Co(II), V(IV), Zn(II), Fe(II), Ni(II) and Cr(III) are described herein. The characterization of the synthesized ligands and complexes were carried out by means of elemental analysis (C,H,N), ¹H and ¹³C NMR and IR spectroscopy, conductivity, magnetic susceptibility and melting point. Through IR and NMR studies, the synthesized ligands were shown to possess the carbonyl (CO) and hydroxylamine (NH₂-OH) groups, characteristics of hydroxamic acid. It was found that the dominant coordination mode in metal-hydroxamic acid complexes was the O, O ’-bidentate chelates in which the ligands were singly deprotonated (hydroxamato). The coordination through the carbonyl oxygen atom and the deprotonated hydroxy group showed a very stable five-membered chelate was formed. Moreover, depending on pH, two (0,0) bonding modes of the ligands are accessible to a series of metal ions like Cu(II), Cr(III), Zn(II), Fe(II) and VO(IV) where in this case, the synthesis took place in acidic environment which making the O, O-bonding modes were more favorable.